Predicting the long-termoutcome of patients admitted with acute heart failure to the emergency department using renal markers. (3rd October 2022) - De Almeida, J P L; Martinho, S; Campos, G; Alves, P; Rosa, J; Ferreira, M; Goncalves, L
Abstract: Introduction: Renal dysfunction is one of the most important comorbidities in patients with chronic heart failure (HF) and frequently accentuated in the setting of acute HF (AHF). Serum creatinine and blood urea nitrogen (BUN) have been classically used as markers of renal dysfunction, despite having several limitations. High (BUN)/creatinine ratio has been associated with higher mortality in patients with HF. We aimed to predict the long-term outcome of patients admitted with acute heart failure to the emergency department using renal markers. Methods: 900 patients admitted to our emergency department diagnosed with AHF were retrospectively analysed. Patients were divided into 4 groups according to BUN and SCr on admission: – BUN ≤33 mg/dL and SCr ≤1.56 mg/dL (group LowBUN/LowCr), n=544; – BUN ≤33 mg/dL and SCr >1.56 mg/dl (group LowBUN/HighCr), n=25; – BUN >33 mg/dL and SCr ≤1.56 mg/dL (group HighBUN/LowCr), n=131; – BUN >33 mg/dL and SCr >1.56 mg/dL (group HighBUN/HighCr), n=200; The primary end-point of this study was the occurrence of all-cause mortality during follow-up. Results: The median (IQR) BUN level on admission was 28.0 (20) mg/dL, median (IQR) SCr level on admission was 1.15 (0.73) mg/d, mean age was 81±7 years, 50.8% (n=457) were women and median follow up was 7 months. A total of 41.2% patients were diabetic, 21.7% had at least mild COPD, CAD was present in 28.9% of cases, 44.0% had valvular heart disease and 68.4% patients had atrial fibrillation. Creatinine, BUN and Cr/BUN ratio predicted survival at 6 months (p<0.05). Survival was the lowest in the group HighBUN/HighCr and the highest in the group LowBUN/LowCr. As expected, BUN/Cr ratio was the highest in group HighBUN/LowCr and the lowest in group LowBUN/HighCr. Conclusions: Despite not having the highest BUN/Cr ratio, patients with BUN >33 mg/dL and SCr >1.56 mg/dL showed the worst prognosis. Funding Acknowledgement: Type of funding sources: None.